The relationship between eating attitude and behaviors with self-esteem of the university students - GÜNEŞ, FATMA ESRA; ÇALIK, KEVSER BURCU (CUMHURIYET UNIV TIP FAK PSIKIYATRI ANABILIM DALI, 2015)
Objective: The purpose of this study is to determine the relationship between eating attitude and behaviors, self-esteems of the university students due to their age, psychosocial issues related to the environment. Methods: For his purpose, it was evaluated the eating attitude and behaviors in two different faculties of the same university (n=450). A cross-sectional random sampling method with the questionnaire was performed including demographic information, the Eating Attitudes Test and the Rosenberg Self-Esteem Test was administered. Results: As a result of statistical analysis a statistically significant difference of the eating attitude test scores with age, weight and average height. It didn't show significant difference between the mean scores of BMI values and mean scores of self-esteem levels. The students were grouped according to cut-off scores of the Eating Attitudes Test (EAT-40) and detected the statistical significant differences between the means of Rosenberg Self-Esteem Test subgroups scores (the self-esteem levels, relying on other people, interpersonal relationships to threats, participate in discussions and psychic isolation). Conclusion: Consequently, the significant relationship was not observed among students studying in different department of education who have eating disorders about their self-esteem risk. Students which studying in health-related department were more sensitivity than other group in the evaluation of eating attitudes and behaviors.
Keywords: University student; eating attitudes; self-esteem; eating attitude and behaviors; DISORDERS; ANOREXIA; ANXIETY; THIN